Training-induced plasticity of auditory localization in adult mammals. - Kacelnik, O; Nodal, F; Parsons, C; King, A (2006)
Accurate auditory localization relies on neural computations based on spatial cues present in the sound waves at each ear. The values of these cues depend on the size, shape, and separation of the two ears and can therefore vary from one individual to another. As with other perceptual skills, the neural circuits involved in spatial hearing are shaped by experience during development and retain some capacity for plasticity in later life. However, the factors that enable and promote plasticity of auditory localization in the adult brain are unknown. Here we show that mature ferrets can rapidly relearn to localize sounds after having their spatial cues altered by reversibly occluding one ear, but only if they are trained to use these cues in a behaviorally relevant task, with greater and more rapid improvement occurring with more frequent training. We also found that auditory adaptation is possible in the absence of vision or error feedback. Finally, we show that this process involves a shift in sensitivity away from the abnormal auditory spatial cues to other cues that are less affected by the earplug. The mature auditory system is therefore capable of adapting to abnormal spatial information by reweighting different localization cues. These results suggest that training should facilitate acclimatization to hearing aids in the hearing impaired.